Use of Gold Sales Profits : Initial Considerations and Options. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In December 2010, the Fund concluded the limited gold sale (403 metric tons) approved by the Board in September 2009. The main purpose of the sale was to generate profits to fund an endowment that would diversify the Fund's income sources away from lending income. In addition, the Board agreed in July 2009, before approving the sale, to a strategy pursuant to which resources linked to the gold sale would contribute to boosting the Fund's concessional lending capacity. Total profits from the gold sale were SDR 6.85 billion. The profits significantly exceeded those assumed in April 2008 when agreement was reached on the key features of the new income model, and in July 2009 at the time of the discussions on a financing package to support reform of the Fund's concessional lending activities. This reflects the substantial increase in the market price of gold throughout the period of the gold sales. With the gold sale complete, it is timely for the Board to revisit the issues relating to the use of the profits. This paper seeks to provide a basis for initial Board consideration of this topic. It focuses primarily on the options for use of the windfall profits above a price of USD 935 per ounce, which was the average price required to generate resources for the endowment at the assumed gold price underlying the new income model and to implement the agreed strategy to provide SDR 0.5-0.6 billion in resources linked to gold sales as part of the 2009 concessional financing package.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet